Studying the Rheological Properties of Non-Newtonian Fluids under the Effect of temperature Using Different Chemical Additives - Hussein Ali, Douaa; A.R. Mohammed, Muhannad (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
This research studies the rheological properties ( plastic viscosity, yield point and apparent viscosity) of Non-Newtonian fluids under the effect of temperature using different chemical additives, such as (xanthan gum (xc-polymer), carboxyl methyl cellulose ( High and low viscosity ) ,polyacrylamide, polyvinyl alcohol, starch, Quebracho and Chrome Lignosulfonate). The samples were prepared by mixing 22.5g of bentonite with 350 ml of water and adding the additives in four different concentrations (3, 6, 9, 13) g by using Hamilton Beach mixer. The rheological properties of prepared samples were measured by using Fan viscometer model 8-speeds. All the samples were subjected to Bingham plastic model. The temperature range studied is from 50 to 200 °F. The results shows that the rheological properties (plastic viscosity, apparent viscosity and yield point) decreased as temperature increased for all prepared samples of non-Newtonian fluids.